Onion carbon preparation method based on metal organic framework and onion carbon
Through a two-step pyrolysis method based on metal organic frames, efficient and low-cost onion carbon particles were prepared, and single-atom iron was introduced on their surface, solving the problems of special equipment, high energy consumption and safety risks in the prior art. , achieving the effect of efficient catalytic oxygen reduction.
Patent Information
- Application Number
- CN202411410973.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-10
AI Technical Summary
In the prior art, when preparing onion carbon, the equipment is special, the energy consumption is high, the production efficiency is low, and the safety risks are present, making it difficult to realize a simple, low-cost and efficient preparation method.
Using a two-step pyrolysis method based on metal organic frames, the synthesis of metal organic frame precursors, preliminary pyrolysis, etching and decomposition of metal particles and secondary pyrolysis were prepared with a diameter of 5 to 20 nm and a carbon layer spacing of 0.34 nm. Uniform onion carbon particles and introduce single-atom iron on its surface.
It realizes efficient and low-cost preparation of onion carbon, the product has high purity and uniformity, is suitable for large-scale production, and significantly improves catalytic activity during catalytic redox reduction.
Smart Images

Figure CN119430159A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic materials, and in particular to a method for preparing onion carbon based on a metal organic framework and onion carbon. Background Art
[0002] Onion carbon is a relatively young member of the nanomaterial family, first discovered by Iijima in 1980. It is a spherical carbon nanoparticle. But unlike fullerenes, they are composed of not one but multiple graphene-like carbon shells stacked concentrically. Depending on the synthesis method and processing parameters, the size of onion carbon is approximately between 2-50nm. Due to its unique physicochemical properties, such as high conductivity, high specific surface area, extremely small nanoparticle size, and high curvature and surface energy, it can be used to enhance the electrochemical performance of certain electrode materials in electrocatalysis, fuel cells, supercapacitors and lithium-ion batteries.
[0003] Functionalizing onion carbon as a catalyst has great potential in catalyzing oxygen reduction. Studies have shown (Angew. Chem. Int. Ed. 2024, e202319370) that the pointed Fe-N4 structure designed on the curved carbon surface can be used for efficient oxygen reduction reactions. The pointed structure can induce a strong local electric field and a dense interfacial water layer, thereby enhancing the kinetics of the proton-coupled electron transfer step, and the electronic structure modulation of the Fe center at the tip also promotes the dissociation of oxygen-containing intermediates during the oxygen reduction process. Similarly, introducing the Fe-N4 structure onto the curved onion carbon surface may also induce a strong local electric field and an interfacial water layer to accelerate the catalytic kinetics of oxygen reduction.
[0004] To date, onion carbon has been synthesized through a variety of techniques, such as arc discharge, electron beam irradiation, heat treatment of nanodiamonds, mechanical grinding, carbon ion beam implantation and detonation reaction. However, the preparation methods such as arc discharge, electron beam irradiation, and carbon ion beam implantation require special instruments and equipment, high energy consumption, and low production efficiency. The heat treatment of nanodiamonds often requires a high temperature and high pressure environment, which increases the manufacturing cost. The number of carbon shells of onion carbon prepared by mechanical grinding is difficult to control, and the production efficiency through mechanical grinding is low. There are great safety risks in the preparation process of onion carbon prepared by detonation reaction, which requires strict safety measures and operating procedures.
[0005] Therefore, there is an urgent need to develop a method for preparing onion carbon that is simple, low-cost and efficient. Summary of the invention
[0006] In order to solve the shortcomings of the prior art, the decomposition of the carbon-containing precursor has the characteristics of low energy loss and simple operation. Therefore, the present invention proposes a method for preparing onion carbon based on pyrolysis metal organic framework. The synthesized onion carbon material has uniform particles with a diameter of 5 to 20 nm and a carbon layer spacing of 0.34 nm. In addition, the introduction of iron elements allows it to be anchored on the curved onion carbon surface in the form of a single atom. The curved structure of onion carbon can reduce the reaction energy barrier when catalyzing the oxygen reduction process, and has more electron transfer to the adsorbed oxygen-containing intermediates, thereby improving the oxygen reduction catalytic activity.
[0007] The technical solution of the present invention is:
[0008] A method for preparing onion carbon based on a metal organic framework comprises the following steps:
[0009] S1. Synthesis of metal organic framework precursor: zinc salt and iron salt are used as metal sources in a reaction tube, and a reaction solvent is added to obtain a mixture. The mixture is dispersed evenly by ultrasound, and then the organic ligand is added dropwise into the reaction tube under stirring. After reacting for 20 to 24 hours, a suspension of the target metal organic framework is obtained. After centrifugation, washing with an organic solution, and drying, the metal organic framework material is obtained.
[0010] S2. Preliminary pyrolysis of metal-organic framework precursors: Spread the metal-organic framework material obtained in S1 on the bottom of a porcelain boat. In an inert atmosphere and normal pressure, heat the temperature from room temperature to 800-1000°C at a rate of 3-8°C / min and keep it at that temperature for 2-3h. After cooling to room temperature, a preliminary carbon material is obtained.
[0011] S3. Etching and decomposing the formed metal particles: the carbon material obtained in S2 is dispersed in an acid solution under the action of ultrasound, and after soaking, the metal nanoparticles on the carbon material are dissolved; then the carbon material is centrifuged, washed and dried to obtain a carbon material powder free of metal particles.
[0012] S4. Secondary pyrolysis of the preliminary pyrolysis carbon material: The carbon material obtained in S3 and melamine are placed in a tube furnace, and the temperature is increased to 900-1000°C at a heating rate of 3-8°C / min and kept at this temperature for 2-3h. After cooling to room temperature, a target carbon material powder with a rich onion carbon structure is obtained.
[0013] Preferably, in S1, the molar ratio of zinc salt to iron salt is (50-500):1.
[0014] Preferably, in S1, the molar ratio of zinc salt to iron salt is 150:1.
[0015] Preferably, the zinc salt is ZnCl2, and the iron salt is FeCl2·4H2O.
[0016] Preferably, in S1, the reaction solvent is a mixed solution of N,N-dimethylformamide, anhydrous ethanol, deionized water and ammonium hydroxide.
[0017] Preferably, in S1, the organic ligand is 1-H-1,2,3-triazole.
[0018] Preferably, in S1, the washing solvent is anhydrous ethanol, and the washing times are 3 to 6 times.
[0019] Preferably, in S1, the washing solvent is anhydrous ethanol, and the washing times are 3 times.
[0020] Preferably, in S1, the drying is vacuum drying, the drying temperature is 60° C., and the drying time is 12 h.
[0021] Preferably, in S2, the inert atmosphere is nitrogen, the initial pressure is -1 to 0 MPa, preferably -0.5 MPa, the initial atmosphere is nitrogen, and the system is kept closed during the heat treatment.
[0022] Preferably, in S2, the heating rate is 5°C / min, the pyrolysis temperature is 1000°C, and the holding time is 2h.
[0023] Preferably, in S3, the acid solution is a 3 mol / L hydrochloric acid solution, and the acid leaching time is 12 to 24 hours.
[0024] Preferably, in S3, the acid solution is a 3 mol / L hydrochloric acid solution, and the acid leaching time is 24 h.
[0025] Preferably, in S3, the washing solution is deionized water, and the washing times are 3 to 6 times, preferably 3 times.
[0026] Preferably, in S4, the mass ratio of melamine to carbon material is (1-3):1.
[0027] Preferably, in S4, the mass ratio of melamine to carbon material is 2:1.
[0028] Preferably, in the tubular furnace in S4, the initial heat treatment pressure is -0.5 MPa, the initial heat treatment atmosphere is N2, and the system is kept closed during the heat treatment process.
[0029] Preferably, in S4, the heating rate is 5°C / min, the pyrolysis temperature is 1000°C, and the holding time is 2h.
[0030] An onion carbon is prepared by the above-mentioned preparation method; the onion carbon has a diameter of 5 to 20 nm and a carbon layer spacing of 0.34 nm.
[0031] The beneficial effects achieved by the present invention are:
[0032] 1. The present invention uses a metal organic framework (MOF) as a precursor, adopts a two-step pyrolysis method, uses high temperature to carbonize the precursor, and uses ammonia and other gases released by the thermal decomposition of melamine to etch the carbon material again. Under this action, the graphene is rearranged in the form of the same spherical core layer to form onion carbon particles of uniform size. The temperature and reaction time in the preparation process can be precisely controlled, the preparation process is simple, and the prepared onion carbon powder has high purity and uniformity, so it has the effect of being able to be mass-produced.
[0033] 2. The introduction of the iron element in the present invention anchors it on the curved onion carbon surface in the form of a single atom. The curved structure of the onion carbon can reduce the reaction energy barrier when catalyzing the oxygen reduction process, and has more electron transfer to the adsorbed oxygen-containing intermediates, thereby improving the oxygen reduction catalytic activity.
[0034] 3. The present invention has low cost in the preparation process, simple operation, controllable conditions, and uniform product size, which has significant advantages among the many methods for synthesizing onion carbon.
[0035] 4. The onion carbon prepared by the present invention has a certain carbon layer spacing and a uniform size distribution. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a flow chart of the preparation method of the present invention;
[0037] Figure 2 This is the onion carbon preparation process obtained in Example 1 of the present invention;
[0038] Figure 3 It is the X-ray diffraction pattern of onion carbon obtained in Examples 1 to 4 of the present invention and Comparative Example 1;
[0039] Figure 4 is a N2 adsorption isotherm diagram and pore size distribution diagram of Example 1 of the present invention;
[0040] Figure 5 is an X-ray photoelectron spectrum diagram of Example 1 of the present invention;
[0041] Figure 6 is a scanning electron microscope image of the onion carbon obtained in Example 1 of the present invention;
[0042] Figure 7 is a scanning electron microscope image of the onion carbon obtained in Example 1 of the present invention;
[0043] Figure 8 2 is a graph showing the oxygen reduction polarization curves of Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0044] To facilitate those skilled in the art to understand the present invention, specific implementations of the present invention are described below with reference to the accompanying drawings.
[0045] It should be noted that the experimental methods described in the examples are conventional methods unless otherwise specified; the reagents and materials are obtained from commercial sources unless otherwise specified.
[0046] like Figure 1 As shown, the present invention provides a method for preparing onion carbon based on a metal organic framework, which specifically comprises the following steps:
[0047] S1. Synthesis of metal-organic framework precursors;
[0048] S2, initial pyrolysis of metal-organic framework precursors;
[0049] S3, etching and decomposition of the formed metal particles;
[0050] S4. Secondary pyrolysis of the primary pyrolysis carbon material.
[0051] Example 1
[0052] S1. Add 4.97g ZnCl2 and 48mg FeCl2·4H2O to a reaction tube, then add a mixed reaction solvent consisting of 50mL N,N-dimethylformamide, 50mL anhydrous ethanol, 75mL deionized water and 20mL ammonium hydroxide to obtain a mixture, disperse the mixture evenly with ultrasound, then add 6.26mL 1H-1,2,3-triazole dropwise to the reaction tube under stirring, and react for 24h to obtain a suspension of Fe@MET-6. After centrifugation, wash with anhydrous ethanol three times, and place in a 60℃ vacuum drying oven overnight to obtain a Fe@MET-6 powder material.
[0053] S2. Spread the Fe@MET-6 powder obtained in S1 on the bottom of a porcelain boat, place it in a tube furnace, and in a N2 atmosphere and normal pressure, increase the temperature from room temperature to 900°C at a heating rate of 5°C / min and keep it for 2h. After cooling to room temperature, a preliminary carbon material is obtained.
[0054] S3. The carbon material obtained in S2 is dispersed in a 3 mol / L HCl solution under the action of ultrasound, and immersed for 24 hours to dissolve the metal nanoparticles on the carbon material; then centrifuged, washed with deionized water three times, and placed in a 60°C vacuum drying oven overnight to obtain a carbon material powder free of metal particles.
[0055] S4, 60 mg of carbon material and 120 mg of melamine obtained in S3 were placed at both ends of a ceramic boat, and the temperature was raised to 1000°C at a rate of 5°C / min in a tube furnace with program-controlled temperature and kept warm for 2 hours, with the initial pressure set to -0.5 MPa. Then the furnace was cooled to room temperature. The target carbon material (p-Fe SAC (150-1)) with rich onion carbon structure was obtained.
[0056] Example 2
[0057] S1. Add 4.90g ZnCl2 and 143mg FeCl2·4H2O to a reaction tube, then add a mixed reaction solvent consisting of 50mL N,N-dimethylformamide, 50mL anhydrous ethanol, 75mL deionized water and 20mL ammonium hydroxide to obtain a mixture, disperse the mixture evenly with ultrasound, then add 6.26mL 1H-1,2,3-triazole dropwise to the reaction tube under stirring, and react for 24h to obtain a suspension of Fe@MET-6. After centrifugation, wash with anhydrous ethanol three times, and place in a 60℃ vacuum drying oven overnight to obtain a Fe@MET-6 powder material.
[0058] S2. Spread the Fe@MET-6 powder obtained in S1 on the bottom of a porcelain boat, place it in a tube furnace, and in a N2 atmosphere and normal pressure, increase the temperature from room temperature to 900°C at a heating rate of 5°C / min and keep it for 2h. After cooling to room temperature, a preliminary carbon material is obtained.
[0059] S3. The carbon material obtained in S2 is dispersed in a 3 mol / L HCl solution under the action of ultrasound, and immersed for 24 hours to dissolve the metal nanoparticles on the carbon material; then centrifuged, washed with deionized water three times, and placed in a 60°C vacuum drying oven overnight to obtain a carbon material powder free of metal particles.
[0060] S4, 60 mg of carbon material and 120 mg of melamine obtained in S3 were placed at both ends of a ceramic boat, and the temperature was raised to 1000°C at a rate of 5°C / min in a tube furnace with program-controlled temperature and kept at this temperature for 2 hours, with the initial pressure set to -0.5 MPa. The mixture was then cooled to room temperature with the furnace. The target carbon material (p-Fe SAC (50-1)) with a rich onion carbon structure was obtained.
[0061] Example 3
[0062] S1. Add 4.99g ZnCl2 and 15mg FeCl2·4H2O to a reaction tube, then add a mixed reaction solvent consisting of 50mL N,N-dimethylformamide, 50mL anhydrous ethanol, 75mL deionized water and 20mL ammonium hydroxide to obtain a mixture, disperse the mixture evenly with ultrasound, then add 6.26mL 1H-1,2,3-triazole dropwise to the reaction tube under stirring, and react for 24h to obtain a suspension of Fe@MET-6. After centrifugation, wash with anhydrous ethanol three times, and place in a 60℃ vacuum drying oven overnight to obtain Fe@MET-6 powder material.
[0063] S2. Spread the Fe@MET-6 powder obtained in S1 on the bottom of a porcelain boat, place it in a tube furnace, and in a N2 atmosphere and normal pressure, increase the temperature from room temperature to 900°C at a heating rate of 5°C / min and keep it for 2h. After cooling to room temperature, a preliminary carbon material is obtained.
[0064] S3. The carbon material obtained in S2 is dispersed in a 3 mol / L HCl solution under the action of ultrasound, and immersed for 24 hours to dissolve the metal nanoparticles on the carbon material; then centrifuged, washed with deionized water three times, and placed in a 60°C vacuum drying oven overnight to obtain a carbon material powder free of metal particles.
[0065] S4, 60 mg of carbon material and 120 mg of melamine obtained in S3 were placed at both ends of a ceramic boat, and the temperature was raised to 1000°C at a rate of 5°C / min in a tube furnace with program-controlled temperature and kept warm for 2 hours, with the initial pressure set to -0.5 MPa. Then the furnace was cooled to room temperature. The target carbon material (p-Fe SAC (500-1)) with rich onion carbon structure was obtained.
[0066] Example 4
[0067] S1. Add 4.95g ZnCl2 and 72mg FeCl2·4H2O to a reaction tube, then add a mixed reaction solvent consisting of 50mL N,N-dimethylformamide, 50mL anhydrous ethanol, 75mL deionized water and 20mL ammonium hydroxide to obtain a mixture, disperse the mixture evenly with ultrasound, then add 6.26mL 1H-1,2,3-triazole dropwise to the reaction tube under stirring, and react for 24h to obtain a suspension of Fe@MET-6. After centrifugation, wash with anhydrous ethanol three times, and place in a 60℃ vacuum drying oven overnight to obtain a Fe@MET-6 powder material.
[0068] S2. Spread the Fe@MET-6 powder obtained in S1 on the bottom of a porcelain boat, place it in a tube furnace, and in a N2 atmosphere and normal pressure, increase the temperature from room temperature to 900°C at a heating rate of 5°C / min and keep it for 2h. After cooling to room temperature, a preliminary carbon material is obtained.
[0069] S3, dispersing the carbon material obtained in S2 in a 3 mol / L HCl solution under the action of ultrasound, soaking for 24 hours to dissolve the metal nanoparticles on the carbon material; then centrifuging, washing with deionized water three times, and placing in a 60°C vacuum drying oven overnight to obtain a carbon material powder without metal particles.
[0070] S4, 60 mg of carbon material and 120 mg of melamine obtained in S3 were placed at both ends of a ceramic boat, and the temperature was raised to 1000°C at a rate of 5°C / min in a tube furnace with program-controlled temperature and kept warm for 2 hours, with the initial pressure set to -0.5 MPa. Then the furnace was cooled to room temperature. The target carbon material (p-Fe SAC (100-1)) with rich onion carbon structure was obtained.
[0071] Comparative Example 1
[0072] Compared with Examples 1 to 4, the main difference is that FeCl2·4H2O is not added when synthesizing MOF.
[0073] S1. Add 5g ZnCl2 to a reaction tube, then add a mixed reaction solvent consisting of 50mL N,N-dimethylformamide, 50mL anhydrous ethanol, 75mL deionized water and 20mL ammonium hydroxide to obtain a mixture, disperse the mixture evenly with ultrasound, then add 6.26mL 1H-1,2,3-triazole dropwise to the reaction tube under stirring, and react for 24h to obtain a suspension of MET-6. After centrifugation, wash with anhydrous ethanol 3 times, and place in a 60°C vacuum drying oven overnight to obtain a MET-6 powder material.
[0074] S2. Spread the MET-6 powder obtained in S1 on the bottom of a porcelain boat, place it in a tubular furnace, and in a N2 atmosphere and normal pressure, increase the temperature from room temperature to 900°C at a heating rate of 5°C / min and keep it for 2 hours. After cooling to room temperature, a preliminary carbon material is obtained.
[0075] S3. To ensure the consistency of the experimental operation, the carbon material obtained in step S2 was dispersed in a 3 mol / L HCl solution under the action of ultrasound, soaked for 24 h, then centrifuged, washed three times with deionized water, and placed in a 60°C vacuum drying oven overnight.
[0076] S4, 60 mg of carbon material and 120 mg of melamine obtained in S3 were placed at both ends of a ceramic boat, and the temperature was raised to 1000°C at a heating rate of 5°C / min in a tube furnace with program-controlled temperature and kept at that temperature for 2 hours, with the initial pressure set to -0.5 MPa. The mixture was then cooled to room temperature with the furnace, and the carbon material powder (NC) of Comparative Example 1 was obtained.
[0077] Figure 2 This is the preparation process of Example 1 of the present invention. It can be seen that after two pyrolysis steps, the initial metal organic framework material (MOF) is transformed into a graphene material with a concentric carbon layer structure.
[0078] Figure 3 The X-ray diffraction patterns of Examples 1 to 4 of the present invention and Comparative Example 1 show broad peaks at 25° and 44°, corresponding to the (002) and (101) crystal planes of graphene, respectively. When the amount of Fe added is large, a phase related to Fe appears, and when the amount of Fe added is small, no phase related to Fe appears.
[0079] Figure 4 The N2 adsorption isotherm and pore size distribution diagram of Example 1 of the present invention show a typical Type I adsorption-desorption isotherm, proving the existence of abundant micropores, which will also be beneficial to material transport and promote oxygen reduction to a certain extent.
[0080] Figure 5 This is the X-ray photoelectron spectrum of Example 1 of the present invention. It can be seen that the carbon material only contains C, N, and O elements. Due to the low content of Fe element, its existence was not detected. In addition, the material does not contain other elements.
[0081] Figure 6 This is a scanning electron microscope image of Example 1 of the present invention, showing a spherical morphology formed by accumulation of small particles.
[0082] Figure 7 This is a transmission electron microscope image of Example 1 of the present invention, in which the presence of onion carbon can be clearly seen.
[0083] Figure 8 It is the oxygen reduction polarization curve diagram of Examples 1 to 5 of the present invention and Comparative Example 1. Example 1 also has excellent oxygen reduction catalytic performance due to the presence of abundant onion carbon.
[0084] In summary, the carbon material synthesized in the present invention has a specific onion-shaped carbon layer structure, a certain carbon layer spacing and a uniform size distribution. In addition, iron is added during the synthesis, so it also shows a certain potential in catalyzing oxygen reduction.
[0085] The above-described embodiments of the present invention do not constitute a limitation on the protection scope of the present invention. Any modification, equivalent substitution and improvement made within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing onion carbon based on metal organic framework, characterized in that: The steps include: S1. Synthesis of metal organic framework precursor: zinc salt and iron salt are used as metal sources in a reaction tube, and a reaction solvent is added to obtain a mixture; the mixture is evenly dispersed by ultrasound, and then the organic ligand is added dropwise into the reaction tube under stirring, and after reacting for 20 to 24 hours, a suspension of the target metal organic framework is obtained; After centrifugation, washing with an organic solution, and drying, a metal organic framework material is obtained; S2. Preliminary pyrolysis of metal organic framework precursor: the metal organic framework material obtained in S1 is spread flat on the bottom of a porcelain boat, and the temperature is raised from room temperature to 800-1000°C at a heating rate of 3-8°C / min under an inert atmosphere and normal pressure, and then kept at this temperature for 2-3 hours. After the temperature is lowered to room temperature, a preliminary carbon material is obtained; S3, etching and decomposing the formed metal particles: dispersing the carbon material obtained in S2 in an acid solution under the action of ultrasound, and dissolving the metal nanoparticles on the carbon material after immersion; then centrifuging, washing and drying the carbon material to obtain a carbon material powder without metal particles; S4. Secondary pyrolysis of the preliminary pyrolysis carbon material: The carbon material obtained in S3 and melamine are placed in a tube furnace, and the temperature is increased to 900-1000°C at a heating rate of 3-8°C / min and kept at this temperature for 2-3h. After cooling to room temperature, a target carbon material powder with a rich onion carbon structure is obtained.
2. The method for preparing onion carbon based on a metal organic framework according to claim 1, characterized in that: In S1, the molar ratio of zinc salt to iron salt is (50-500):
1.
3. The method for preparing onion carbon based on metal organic framework according to claim 1, characterized in that: The zinc salt is ZnCl2, and the iron salt is FeCl2·4H2O.
4. The method for preparing onion carbon based on metal organic framework according to claim 1, characterized in that: In S1, the reaction solvent is a mixed solution of N,N-dimethylformamide, anhydrous ethanol, deionized water, and ammonium hydroxide.
5. The method for preparing onion carbon based on metal organic framework according to claim 1, characterized in that: In S1, the organic ligand is 1-H-1,2,3-triazole.
6. The method for preparing onion carbon based on metal organic framework according to claim 1, characterized in that: In S1, the washing solvent is anhydrous ethanol, and the number of washing times is 3 to 6 times.
7. The method for preparing onion carbon based on metal organic framework according to claim 1, characterized in that: In S3, the acid solution is a 3 mol / L hydrochloric acid solution, and the acid leaching time is 12 to 24 hours.
8. The method for preparing onion carbon based on metal organic framework according to claim 1, characterized in that: In S4, the mass ratio of melamine to carbon material is 2:
1.
9. The method for preparing onion carbon based on metal organic framework according to claim 1, characterized in that: In the tubular furnace S4, the initial heat treatment pressure is -0.5MPa, the initial heat treatment atmosphere is N2, and the system is kept closed during the heat treatment process.
10. An onion carbon, characterized in that: The onion carbon is prepared by the preparation method described in any one of claims 1 to 9; the diameter of the onion carbon is 5 to 20 nm, and the distance between carbon layers is 0.34 nm.
Citation Information
Patent Citations
Compound type fuel cell cathode catalyst NGPC / NCNTs and preparation method thereof
CN106159287A
Cited By
Pt-Co diatomic site self-supporting integrated electrode and preparation method and application thereof
CN122147430A
Pt-co bimetallic site self-supported integrated electrode and preparation method and application thereof
CN122147430B